AI-Driven Smart Classrooms and Emerging Technologies in Higher Education: A Data Analysis - Parkavi. A,; Pushpalatha M N,; Nandini S B, (Language, Literature and Education: Research Updates Vol. 2, 2025)
This study explores the integration of artificial intelligence (AI), data analytics, and emerging technologies in smart classrooms to enhance teaching-learning experiences, particularly in high school and higher education. It examines AI-driven tools, virtual reality programs, and data analysis techniques, with a focus on their impact on student engagement, comprehension, and outcome-based education. Leveraging the R programming language, the study assesses how data-driven insights improve learning outcomes, especially in online and hybrid education models. Additionally, the research investigates the acceptance of emerging technologies, including augmented reality, virtual reality, and mobile learning, using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Through empirical findings and a survey of 120 students, the study identifies key benefits, challenges, and future directions for AI and data analytics in education. The findings provide valuable implications for educators, policymakers, and stakeholders in optimizing instructional methodologies and fostering a technologically advanced learning environment.